2013
DOI: 10.1128/jb.00339-13
|View full text |Cite
|
Sign up to set email alerts
|

Pouring Salt on a Wound: Pseudomonas aeruginosa Virulence Factors Alter Na+ and Cl- Flux in the Lung

Abstract: Pseudomonas aeruginosa is a ubiquitous opportunistic pathogen with multiple niches in the human body, including the lung. P. aeruginosa infections are particularly damaging or fatal for patients with ventilator-associated pneumonia, chronic obstructive pulmonary disease, and cystic fibrosis (CF). To establish an infection, P. aeruginosa relies on a suite of virulence factors, including lipopolysaccharide, phospholipases, exoproteases, phenazines, outer membrane vesicles, type III secreted effectors, flagella, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 88 publications
2
46
0
1
Order By: Relevance
“…aeruginosa possesses an arsenal of virulence factors enabling it to invade host cells and circumvent host defenses (35,42). These mechanisms of virulence include secreted factors such as proteases, elastase, pyocyanin, exotoxin A, phospholipase C, and exoenzyme S and also cell-associated factors such as lipopolysaccharide (LPS), flagella, and pili (35,43).…”
Section: Overview Of P Aeruginosa Clinical Impact: Virulence Factorsmentioning
confidence: 99%
“…aeruginosa possesses an arsenal of virulence factors enabling it to invade host cells and circumvent host defenses (35,42). These mechanisms of virulence include secreted factors such as proteases, elastase, pyocyanin, exotoxin A, phospholipase C, and exoenzyme S and also cell-associated factors such as lipopolysaccharide (LPS), flagella, and pili (35,43).…”
Section: Overview Of P Aeruginosa Clinical Impact: Virulence Factorsmentioning
confidence: 99%
“…Phenazines display a broad spectrum of (toxic) activity toward prokaryotic and eukaryotic organisms, varying according to the nature and position of the substituent on the heterocyclic ring. They are considered as virulent factor pf P. aeruginosa (Ballok and O'Toole, 2013), but no standard toxicity data have been found in this report for these substances. Phenazines are considered redox-active compounds as well as a cytotoxic pigment.…”
Section: Phenazinesmentioning
confidence: 90%
“…They are considered as virulent factor pf P. aeruginosa (Ballok and O'Toole, 2013), but no standard toxicity data have been found in this report for these substances. Phenazines are considered redox-active compounds as well as a cytotoxic pigment.…”
Section: Phenazinesmentioning
confidence: 99%
“…3 P. aeruginosa secretes the CFTR inhibitory factor (Cif) that blocks the post-endocytic deubiquitination of CFTR and thus facilitates its lysosomal degradation. 4 Cif is a member of the α/β hydrolase family and has demonstrated epoxide hydrolase (EH) activity. 5 Using site directed mutations and inhibitors, we observed that Cif EH activity is critical for the inhibition of CFTR deubiquitination.…”
Section: Introductionmentioning
confidence: 99%